TI_GERICHTE 32.2020.25 vom 21. Januar 2020 , Carrozziere indipendente. LAI-LAINF. Prima domanda. Grado AI: 18% - TI Tribunale d'appello (2020)
Carrozziere indipendente. LAI-LAINF. Prima domanda. Grado AI: 18%